Physical Condition Analysis of Junior Athletes of LAVANI Volleyball Club - Bujang; Arisman; Aridhotul Haqiyah; Mia Kusumawati; Tatang Iskandar (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
This study aims to analyze the physical condition of junior athletes of the LAVANI Cikeas Bogor volleyball club including cardiovascular endurance, muscle strength, muscle explosive power, flexibility, and body composition. This physical component is important to support the appearance of athletes in volleyball. The method used is descriptive research with measurements using valid and reliable field tests. The study population was all junior athletes of the LAVANI Cikeas Bogor volleyball club totaling 30 people with total sampling techniques. The instruments used include multi-stage running tests, push-up tests, vertical jump tests, sit and reach tests, and anthropometric measurements. The results showed that the average cardiovascular endurance of athletes was in the good category, arm and shoulder muscle strength in the sufficient category, leg muscle explosive power in the less category, flexibility in the good category, and body composition of most athletes was in the ideal range. Overall, the physical condition of the junior athletes of the LAVANI Cikeas Bogor volleyball club is considered quite good but still needs to be improved, especially in the explosive power component of the leg muscles to support optimal performance in playing volleyball.